Relationship between smoking and adaptation to pregnancy and body image - Oflaz, Sema; Amanak, Keziban; Kulaksız, Deniz (Journal of Dependence, 2024)
Objective: This study aimed to explore the correlation between smoking habits and the adjustment to pregnancy, as well as body image, among three distinct groups of pregnant women: those who have never smoked, those who quit smoking during pregnancy, and those who continued smoking during pregnancy. Method: The research involved 102 pregnant women, and data were gathered using a Personal Information Form, the Prenatal Self-Assessment Scale, and the Body Image Questionnaire. Results: The study revealed that the mean scores on the Prenatal Self-Assessment Scale were significantly higher among pregnant women who quit smoking during pregnancy and those who smoked during pregnancy compared to those who had never smoked. Furthermore, pregnant women who smoked during pregnancy scored significantly lower on the Body Image Questionnaire in comparison to both women who never smoked and those who quit smoking during pregnancy. Additionally, the research demonstrated a moderate and negative correlation between the mean scores of adaptation to pregnancy and body image among all pregnant participants. Conclusion: The findings suggest a detrimental impact of smoking on both pregnancy adaptation and body image. It was evident that pregnant women experiencing poor adaptation to pregnancy also tended to have negative body image perceptions.